Identificação de genes com alta diferenciação entre populações humanas: inferências evolutivas e implicações biomédicas - Giordano Bruno Soares Souza (2010)
Genetic diversity is related to phenotypic differentiation among human populations. Even though most of this variation occurs among individuals and interaction with the environment plays a key role in phenotypic determination, the study of variants that are genetic structured in human populations is crucial in two major fields of biology: evolution and medicine. Investigating loci with differentiated allelic frequency in human populations allows improvement of case-control association studies in admixed populations and discovery of genetic polymorphisms that have experienced natural selection. In this context, we studied hierarchical genetic structure of 1442 SNPs located in 411 genes related to immune response, carcinogenesis and pharmacogenetics. This genetic characterization was made for 1198 individuals from 60 worldwide populations belonging to HGDP, SNP500Cancer and Native-American populations of Ecuador and Peru. The following results emerge from Analysis of Molecular Variance approach: we identified 196 polymorphisms allocated in 111 genes that can lead to spurious association in case-control studies performed in tri-hybrid populations like Brazilian population. In this context, many genetic markers were recognized in alternative models of bi-hybrid populations formed from European, Native-American and West African populations. We show 36 SNPs highly differentiated among East Asians and Amerindians that could have suffered positive selection or allele surfing. Using loci heterozigosity we appointed putative loci under one of three types of natural selection: positive, purifying and balancing. The combined use of distinct genetic statistics in different populations can improve not only design of epidemiological studies as can clarify aspects of prevalence in human diseases and to tell a little about human history.